FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA KECELAKAAN KERJA PEMBANGUNAN PLTA PADA KARYAWAN PT GLOBAL DI DESA SIMANABUN KECAMATAN SILAU KAHEAN KABUPATEN SIMALUNGUN TAHUN 2014 - emli cuan saragih (Lingkungan dan Kesehatan Kerja, 2014)
Work accident is one of the problems that often occur in workers in the company. PT Global in implementing hydropower development in 2013, there were 32 cases of occupational accidents on employees consisting of 9 cases are not using personal protective equipment such as gloves, 5 cases are not using safety helmets, 8 cases are not using boots, and 10 cases caused while working less cautious. This research was conducted to determine the factors that influence the incidence of workplace accidents hydropower development on employees PT Global in Simanabun village Sub District Kahean Glare Simalungun in 2013. This research type is analytic. Population are field employees of PT Global who are implementing a hydropower dam construction work , and the sample in this research are the total population of PT Global field employees numbering 98 people. The data in this research is primary data (questionnaire). Test data using multiple logistic regression statistical tests. The results showed that there was no effect of standard operating procedures, direction, knowledge, and attitudes toward work accident occurrence, and there is also the influence of personal protective equipment, measures, and the work environment on the incidence of workplace accidents. The conclusion that the factor of personal protective equipment, measures and work environment influence the incidence of workplace accidents. It is suggested to the company making signs about safety in areas that could potentially happen accidents. Supervisors (foremen) should probably familiarize employees field dam to wear protective equipment themselves by providing training so that employees are accustomed to wearing it. Keywords : Accidents , Construction of Hydropower